The synthesis of vertically aligned carbon nanotubes on nanostructured porous silicon template by in-situ catalyst double thermal chemical vapour deposition method / Noor Asnida Asli - Asli, Noor Asnida (Institute of Graduate Studies, UiTM, 2015)
Nanastructured porous silicon template (NPSiT) was successfully prepared from [100] orientation p-doped silicon (Si) substrate by photo-electrochemically anodization method with optimization parameters of etching time and annealing temperature while the rest of parameters were fixed. Uniform porous structures, optimum surface roughness and high intensity of photoluminescence (PL) of NPSiT as an optimized samples. The optimized NPSiT was used as template to synthesis vertically aligned carbon nanotubes (VACNT). VACNT were synthesized on NPSiT using double thermal chemical vapour deposition (DTCVD) method with camphor oil as carbon source and ferrocene (Fe) as a catalyst. The synthesis was carried out by the in-situ catalyst with floated method in a DTCVD reactor without any pre-treatment of catalyst. The process was called in-situ catalyst due to same vaporization point, 180°C of camphor and ferrocene. High percentage of vertically aligned, smallest diameter, uniform length, high graphite crystallinity and high growth rate of VACNT on NPSiT has been successfully synthesized with short synthesis time at 15 min. Single-Walled Carbon Nanotubes (SWCNT) was found at 15 min synthesis time gave lowest ID/IG ratio. Parametric studies were done such as ratio of catalyst to carbon source, synthesis temperature and synthesis time to determine optimum parameter in obtain VACNT on NPSiT…